Simulation of Spatially Correlated Multipoint Ground Motions in a Saturated Alluvial Valley - Ying He; Xueling Chen; Zhongxian Liu; Dejian Yang; Hai Zhang (Shock and Vibration)
Based on Biot’s theory, the boundary element method, and spectral representation method, an effective simulation method for multiple-station spatially correlated ground motions on both bedrock and surface is developed, incorporating the spectral density function, coherence function, and site transfer function that consider both the wave scattering effect and the medium saturation. The accuracy and feasibility of the present method are validated by a typical numerical example. Our results indicate that the local site conditions and the saturation property of the medium significantly affect the multipoint spatially correlated earthquake ground motions, especially in the long-period range. It is necessary to use spatially varying ground motions with the rational consideration of local site effects and medium saturation as input during the seismic analysis of large-span structures.